Photoshop CS4 top 100 simplified tips & tricks - Kent, Lynette (Read less-learn more, 2009)
"Packed with 100 cool and useful tips and tricks, this visual tutorial investigates the bells and whistles that come with the new CS4 release"--Resource description page.